Recurrent NAB2–STAT6 gene fusions and oestrogen receptor‐α expression in pulmonary adenofibromas. Issue 6 (24th February 2017) - Fusco, Nicola; Guerini‐Rocco, Elena; Augello, Claudia; Terrasi, Andrea; Ercoli, Giulia; Fumagalli, Caterina; Vacirca, Davide; Braidotti, Paola; Parafioriti, Antonina; Jaconi, Marta; Runza, Letterio; Ananthanarayanan, Vijayalakshmi; et al.
Abstract : Aims: Pulmonary adenofibromas are rare benign fibroepithelial tumours of the lung with unknown histogenesis and an indolent clinical behaviour. Their stroma resembles that of solitary fibrous tumours, whereas the glands are composed of respiratory epithelium organized in a phyllodes‐like architecture. Differentiation of pulmonary adenofibromas from other more aggressive intrathoracic tumours is clinically relevant. However, their biology is unknown. Here, we sought to characterize pulmonary adenofibromas at a clinicopathological level and to define whether they could be underpinned by a highly recurrent somatic genetic alteration akin to tumours with similar morphology. Methods and results: Seven pulmonary adenofibromas were subjected to immunohistochemical analysis for thyroid transcription factor 1 (TTF1), napsin A, cytokeratin 7, E‐cadherin, CD99, CD34, CD31, STAT6, oestrogen receptor (ER), progesterone receptor, androgen receptor, bcl‐2, and vimentin, as well as electron microscopy and capillary sequencing on microdissected samples to evaluate the presence of NAB2 – STAT6 fusion genes and MED12 exon 2 mutations in their discrete components. A control group comprising pulmonary solitary fibrous tumours, pulmonary hamartomas and breast fibroadenomas was also analysed. We confirmed that the stromal elements of pulmonary adenofibromas pertain to the fibroblastic lineage, and show ER overexpression in 71% of cases, whereas the epithelium consists of TTF1‐positive, E‐cadherin positive bronchiolar elements. A highly recurrent NAB2 – STAT6 fusion variant (exon 4–exon 2) was detected in the stroma but not in the epithelium. No MED12 mutations were identified. Conclusions: Here, we demonstrate that pulmonary adenofibromas are neoplastic lesions harbouring the molecular hallmark of solitary fibrous tumours.